2x=(7x-y)+(6-4y)

Simple and best practice solution for 2x=(7x-y)+(6-4y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x=(7x-y)+(6-4y) equation:


Simplifying
2x = (7x + -1y) + (6 + -4y)

Remove parenthesis around (7x + -1y)
2x = 7x + -1y + (6 + -4y)

Remove parenthesis around (6 + -4y)
2x = 7x + -1y + 6 + -4y

Reorder the terms:
2x = 6 + 7x + -1y + -4y

Combine like terms: -1y + -4y = -5y
2x = 6 + 7x + -5y

Solving
2x = 6 + 7x + -5y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
2x + -7x = 6 + 7x + -7x + -5y

Combine like terms: 2x + -7x = -5x
-5x = 6 + 7x + -7x + -5y

Combine like terms: 7x + -7x = 0
-5x = 6 + 0 + -5y
-5x = 6 + -5y

Divide each side by '-5'.
x = -1.2 + y

Simplifying
x = -1.2 + y

See similar equations:

| 6-2(w+1)=6w-2(6+w) | | 7(s-4)+13= | | .47=log(x) | | 0.11x=56 | | 5-x=8-x-3 | | 4x-17=4x | | 16=4(1+7x)-8(3x-5) | | f=6/5(n-18) | | 8-3(2x+3)=11 | | 4x-5=4x+12 | | -3(2x+3)=11 | | g=5/3(p-49) | | 4-5-13-18+2= | | 14=8x+7-x | | 458000*9= | | ln(x-4)=6 | | 90=2(7x+3) | | 3x+5x-8+4-11+17x-42+7x=-6 | | -252=-7(-6x+6) | | -91=-7(3r+4) | | 8w-14=434 | | 3(-5x+2)=-84 | | 6x+27=36 | | 7x+9y=103 | | 2x^2+-2x^2= | | (5y+3)(1+y)=0 | | (x-3)-2=6-2(x-1) | | -126=-3(-6-8n) | | -18-3p=-(p+4) | | 9y^3-11x^2+2-13y^3-15x^2= | | 2b+3b-4b+3=17 | | 10y^3-11x^2+2-12y^3-13x^2= |

Equations solver categories